Design and implementation of a solar integration in electric smart bench. Issue 1 (February 2021) - Kango, Riklan; Hadiyanto,; Pongtularan, Ezra Hartarto
Abstract: Energy problems that hit the world have implications for savings in all fields, including lighting public spaces. However, lighting conventional public areas is an inappropriate step because the monthly electricity costs required are already very expensive. This paper proposes new solutions for alternative sources of electrical energy in open spaces. We validate this solution by implementing a solar cell in a park bench object. The experimental results show that the proposed solution has the same performance as conventional lighting. Electric park benches can operate longer by using a solar cell with an output power of 26.76 Watt-peak hours. With the enormous potential of solar power, the application of solar cells in an open environment is very suitable. With this electric bench, it is still energy efficient and green energy.